2012
DOI: 10.1038/onc.2012.38
|View full text |Cite
|
Sign up to set email alerts
|

p53 is activated in response to disruption of the pre-mRNA splicing machinery

Abstract: In this study, we show that interfering with the splicing machinery results in activation of the tumour-suppressor p53. The spliceosome was targeted by small interfering RNA-mediated knockdown of proteins associated with different small nuclear ribonucleoprotein complexes and by using the small-molecule splicing modulator TG003. These interventions cause: the accumulation of p53, an increase in p53 transcriptional activity and can result in p53-dependent G(1) cell cycle arrest. Mdm2 and MdmX are two key repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 67 publications
14
47
0
Order By: Relevance
“…We recently reported that alteration of alternative splicing pathway activates p53, regulates p53-target gene expression and induces a p53-dependent G1 cell cycle arrest in HCT116 cells. 14 Here we determined whether combined knockdown of p53b and p53g by siP53-i9 affects MCF7 cell response to Figure 6). To exclude difference between siCT and siP53-i9-transfected cells due to variation in basal apoptosis, MTT assays were normalized at the day of TG003 addition ( Figure 6b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported that alteration of alternative splicing pathway activates p53, regulates p53-target gene expression and induces a p53-dependent G1 cell cycle arrest in HCT116 cells. 14 Here we determined whether combined knockdown of p53b and p53g by siP53-i9 affects MCF7 cell response to Figure 6). To exclude difference between siCT and siP53-i9-transfected cells due to variation in basal apoptosis, MTT assays were normalized at the day of TG003 addition ( Figure 6b).…”
Section: Resultsmentioning
confidence: 99%
“…However, the impact of TG003 on p53a protein is cell line-dependent, p53a expression being either increased or decreased, supporting a cell typedependent effect of TG003. 14 Early studies reported that p53b has some tumor suppressor-like activity in non-treated normal fibroblasts and cancer cells, p53b promoting apoptosis and senescence by differentially regulating gene expression. 3,6 Consistently, endogenous p53b and p53g expression promotes G1 cell cycle arrest and basal apoptosis in MCF7 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear speckles are cellular bodies that contain transcription and pre-mRNA processing components (24). Knockdown of PB target SF3B1 causes a "mega-speckles" phenotype in which the speckles coalesce into large bodies (25). PB treatment of cells also induces formation of mega-speckles (8).…”
Section: Synthesis Of Pb Structuralmentioning
confidence: 99%
“…We found altered expression of the regulators serine/arginine-rich splicing factor 3 (SRSF3), splicing factor 3A3 (SF3A3), heterogeneous nuclear ribonuclear proteins Q and A1, small nuclear ribonuclear proteins A′ and E, regulation of nuclear pre-mRNA domain-containing protein 2 (RPRD2), RNA-binding proteins 22, 4b, 39, 47, and MS, and the RNA helicase DHX30 (Table 1). Perturbation of the splicing machinery also can activate the p53 pathway (71,72).…”
Section: Functional Classes Of Proteins and Pathways Changed By Exposmentioning
confidence: 99%